Analysis Of Influence On Pt. Astra Agro Lestari Tbk Financial Performance In Measuring Financial Statements In 2018-2019 Period - Yola Amanda; Setyo Riyanto (Journal of Social Science, 2020)
This research aims to see how the financial performance of PT. Astra Agro Lestari Tbk in the period 2018-2019 by measuring financial statements using ratio analysis. Ratio analysis is an appropriate method for measuring financial performance using Liquidity, Solvency, Activity, and Profitability ratios. Data and information in this study were obtained from the Indonesia Stock Exchange. The result of this calculation is that the liquidity ratio has increased, which is good for the company. The solvency ratio shows that the company is not sufficient to guarantee the debt provided by creditors so that the company can be said to be in bad condition. The ratio of the company’s activity has increased and also decreased. Whereas the profitability ratio results always decrease so the company has suffered losses, the company must increase its financial performance again.